Analisis Yuridis Penyelesaian Sengketa Pada Pengadilan Hubungan Industrial Terkait Seseorang Yang Menganggap Dirinya Memiliki Hubungan Kerja Dengan Perusahaan - Sumantri, Kukuh Dwi Gilang; Nadappdap, Binoto; Sri Widiarty, Wiwik (CV. Green Publisher Indonesia, 2025)
This study aims to provide a juridical analysis of dispute resolution in the Industrial Relations Court involving an individual who claims to have an employment relationship with a company, focusing on Case Decision No. 141/Pdt.Sus-PHI/2023/PN.Jkt.Pst. Employment disputes frequently arise due to unclear worker status and the legal relationship between individuals and companies. This research applies a normative juridical method using statute and case approaches. Data were obtained through library research, including primary, secondary, and tertiary legal materials. The findings indicate that the elements of an employment relationship, as regulated by law, must be objectively fulfilled for a person to be recognized as a worker. In the case study, the court assessed the existence of an employment relationship based on relevant legal facts. This research contributes to the understanding of legal protection for workers with disputed status and highlights the importance of justice in resolving industrial relations disputes.